The new EU climate and energy strategy in a time of war: Energy security first - Jakob Dreyer; Christine Nissen (Danish Institute for International Studies (DIIS), 2023)
The Russian invasion of Ukraine challenges the liberal peace project that has always been at the heart of the European Union. The political project that led to the EU was founded on the idea that economic trade and political cooperation promote reconciliation and create a more peaceful and prosperous Europe and world. Incrementally, the merger of interests and ideals justified closer political and economic relations among EU member states and with third countries. In its relations with Russia, the economic peace project helped to justify the development of energy imports to European countries over the course of generations. With the inclusion of several former Soviet states the EU in the early 2000s, Poland and several of the other new member states expressed their concerns with the security implications of the close trade ties with Russia. Energy imports to Germany and other key member states continued to increase despite a lack of political integration or cooperation with Russia. Now, the full-scale military invasion of Ukraine turned EU member states into co-financers of the Russian invasion through their energy imports, undermined the security of European energy supply, and caused economic turmoil across the continent. The security, economic, and political implications revealed that one of the fundamental prerequisites of the liberal peace project was not realized: the principle of interdependence. In other words, key EU member states turned out to be more dependent on Russia than vice versa. This realisation is catalysing a process whereby the EU is reconsidering its international dependencies, thereby reforging itself to become a more autonomous actor in international relations. [...]
Keywords: 300; EU; climate; energy; Ukraine; war; security; autonomy agenda; RepowerEU Action Plan; energy security